Faculty Advisors’ Experiences with International Graduate Students - Nguyen, Huynh Mai (Journal of International Students, 2013)
The current study explored the experiences of faculty advisors working with international graduate students (IGS). Data was collected through semi-structured interviews and a demographic survey and was analyzed using open, axial, and selective coding strategies. Three central categories emerged from the analysis: (a) advisors’ perceptions of IGS, (b) lessons learned by advisors, and (c) indicators of success. A model for advisors’ experiences emerged using the data gathered. Overall, advisors reported positive experiences with current and former advisees. Advisor perceptions’ of IGS were used to develop strategies and approaches that they believe enhance their experiences as well as the advisees’ experiences. At the core of the Advisor Experiences Model are variables that convey success regarding the relationship between advisors and their IGS. These variables are: (a) sustained relationships and (b) student success rates. Advisors all reported that the sustained relationship is one of the most rewarding aspects of being an advisor.